MASA KERJA PANJANG, FINANCIAL MENINGKAT: APAKAH SELALU SEJALAN? (METODE KUANTITATIF) - Adhi Danar Dono; Aji Wijayanto; Lalang Dintara; Taufiq Siamuddin; Yudi Prastyo (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to determine whether there is a significant influence between length of service on the increase or income of financial compensation received by employees in Bekasi City and South Jakarta. The method used in this research is simple linear regression, with tenure as the independent variable (X) and increase in financial compensation as the dependent variable (Y). Data was obtained through distributing questionnaires to respondents working in the region. The results of the analysis show that there is a strong relationship between tenure and increased compensation, with a correlation coefficient (R) value of 0.7969. In addition, the coefficient of determination (R²) value of 0.6352 indicates that 63.52% of the variation in increased compensation can be explained by tenure, while the rest is influenced by other factors. The significance test through ANOVA resulted in a Significance F value of 2.59352 × 10-¹⁴, which is smaller than the alpha value (0.05), so the regression model is statistically significant. Thus, it can be concluded that tenure has a significant influence on the increase in financial compensation received by employees. These results are expected to be taken into consideration for companies in designing fair and tenure-based compensation policies.